The principles of state and government in Islam - Asad, Muhammad (Islamic Book Trust Kuala Lumpur, 2000)
The very fact that none of the existing Muslim countries has so far achieved a form of government that could be termed genuinely Islamic, makes a discussion of the principles that underlie the constitution of Islamic state imperative. This book is an attempt to keep that discussion alive.